2005
DOI: 10.2320/matertrans.46.118
|View full text |Cite
|
Sign up to set email alerts
|

Damping Properties of Ductile Cu-Al-Mn-Based Shape Memory Alloys

Abstract: The damping property tan 0 of Cu-Al-Mn-based alloys, where tan 0 is nearly equal to internal friction Q À1 , was investigated using a Dynamic Mechanical Spectrometer (DMS). It was found that the dependences of frequency and strain amplitude on tan 0 are significantly different between the parent + martensite two-phase and the martensite single-phase states, i.e., tan 0 is mainly influenced by frequency in the two-phase state and by strain amplitude in the martensite state. It was also found that the relative g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 11 publications
3
20
0
Order By: Relevance
“…Araya et al [15] showed that in Cu-Al-Be wires with D = 0.5 mm, ∆E/E remains nearly constant when d decreases from ~300 to ~100 μm, but starts to decline below this point. A similar size effect is observed in Cu-Al-Mn sheets [20] and wires [21], where  tan decreases with decreasing d/D. Such decrease in damping at smaller d/D is attributed to three-dimensional grain constraint [20,21].…”
Section: Introductionsupporting
confidence: 58%
“…Araya et al [15] showed that in Cu-Al-Be wires with D = 0.5 mm, ∆E/E remains nearly constant when d decreases from ~300 to ~100 μm, but starts to decline below this point. A similar size effect is observed in Cu-Al-Mn sheets [20] and wires [21], where  tan decreases with decreasing d/D. Such decrease in damping at smaller d/D is attributed to three-dimensional grain constraint [20,21].…”
Section: Introductionsupporting
confidence: 58%
“…It has also been applied in the development of flexible glass frames, bra under wires, and many biomedical applications as a result of their DOI good corrosion resistance and biocompatibility [6]. The high damping capacity of SMAs has made them suitable for applications where reduced noises and vibrations are required [7]. Thus considering the current areas of application of SMAs and its potential for wider use, it is expected that studies on how to improve their overall material properties will remain of interest in the years ahead.…”
Section: Introductionmentioning
confidence: 99%
“…The trigger for wide research of Cu-Al-Mn alloys in recent years is their easy manufacturing, low cost as well as good properties, especially electric properties and thermal conductivity. The special emphasis of investigations are Cu-Al-Mn shape memory alloys (SMA), that shows unique properties of remembering their shape as well as recovering to original shape under temperature changes or plastic deformation [1][2][3][4]. Cu-Al-Mn alloys display advantage in technological applications over other Cu-based SMA alloys, such as Cu-Al-Ni, Cu-Al-Zn etc., according to significantly higher ductility and ability of cold deformation [5,6].…”
Section: Introductionmentioning
confidence: 99%